StRAP2.3, an ERF‐VII transcription factor, directly activates StInvInh2 to enhance cold-induced sweetening resistance in potato. (1st April 2021) - Shi, Weiling; Song, Yuhao; Liu, Tiantian; Ma, Qiuqin; Yin, Wang; Shen, Yuchen; Liu, Tengfei; Jiang, Chunyan; Zhang, Kai; Lv, Dianqiu; Song, Botao; Wang, Jichun; et al.
Abstract: Potato invertase inhibitor ( StInvInh2 ) positively regulates cold-induced sweetening (CIS) resistance by inhibiting the activity of vacuolar invertase. The distinct expression patterns of StInvInh2 have been thoroughly characterized in different potato genotypes, but the related CIS ability has not been characterized. The understanding of the regulatory mechanisms that control StInvInh2 transcription is unclear. In this study, we identified an ERF‐VII transcription factor, StRAP2.3, that directly regulates StInvInh2 to positively modulate CIS resistance. Acting as a nuclear-localized transcriptional activator, StRAP2.3 directly binds the ACCGAC cis-element in the promoter region of StInvInh2, enabling promoter activity. Overexpression of StRAP2.3 in CIS-sensitive potato tubers induced StInvInh2 mRNA abundance and increased CIS resistance. In contrast, silencing StRAP2.3 in CIS-resistant potato tubers repressed the expression of StInvInh2 and decreased CIS resistance. We conclude that cold-responsive StInvInh2 is due to the binding of StRAP2.3 to the ACCGAC cis-element in the promoter region of StInvInh2 . Overall, these findings indicate that StRAP2.3 directly regulates StInvInh2 to positively modulate CIS resistance, which may provide a strategy to improve the processing quality of potatoes.